Structural analogues of complex magnetic phases - Wolpert, EH (2020)
This thesis studies the phase behaviour of a variety of complex solid structures. The principal approach taken is to develop a suitable coarse graining of the degrees of freedom in order to allow a representation in terms of interaction models.